Linguistic realizations and lexical bundles in the discussion section of medical research articles - Al-Shujairi, Yasir Bdaiwi Jasim (2020)
A rhetorical move is a sentence or group of sentences that serves a communicative function in a text while a lexical bundle is a group of words that frequently occur together. Both bundles and moves are considered building blocks and contribute to the construction of meaning in the discourse. Recent studies have been influenced by bundle-move connection approach to combine moves and lexical bundles. So far, literature lacks studies that connect lexical bundles to the moves and steps in the discussion section of RAs (research articles) in the field of medicine. Thus, this research attempted to fill the gap by examining the moves, linguistic features and lexical bundles in the discussion of MRAs. Concerning the method, quantitative analysis was used to examine the frequency of occurrences in both the moves and the lexical bundles in each move and step while qualitative analysis was used to explain moves, linguistic features and bundles associated with the MRAs’ discussion section. The corpus size of this research was 50 discussions of high impact factor RAs in the field of medicine. Additionally, the study employed two analytical frameworks: a model of three moves to analyse the communicative functions and a categorisation of 12 structural patterns for the analysis of the lexical bundles. The findings of move analysis revealed six moves and nine steps. Move 2 (Highlighting Overall Research Outcome), move 3 (Explain Specific Research Outcomes), move 4 (Contrasting Present and Previous Outcomes) and move 6 (Stating Research Conclusion) were considered obligatory moves as each occurred with a frequency of 100%. Move 1 (Background Information) which is a newly found move had 64% occurrences and thus it was considered a conventional move. The analysis also revealed 2 steps (Referring to Literature and Making a Claim) under move 4 and 4 steps (Strengths and Weaknesses of a Research, Indicating Research Limitations, Promoting Further Research and Concluding the Main Results) under move 6. Concerning the linguistic features, move 1 was realised by procedural verbs (i.e., use, examine) while move 2 was mainly realised by reporting verbs (i.e., show, find), first person plural pronoun and past tense. In move 3, interpreting verbs (i.e., explain, reflect) and causative conjunctions (due to, because) were realised in step 2. In move 4, comparative and contrasting devices (i.e., in contrast and similar to) characterised step 1 and hedges such as modal hedging (i.e., may, might) and hedging verbs (i.e., seem, imply) characterised step 2. The rest of the moves/steps were mainly realised by explicit lexemes (i.e., implications, limitations, strengths, further). Regarding the lexical bundles identification, the highest number of bundles was associated with move on Highlighting Overall Research Outcome, move 3 step Interpreting the Outcome and move 4 step Referring to Literature. A total of 10 bundles such as we found that and our study shows that were associated with move 2, 14 bundles such as the effect of and could be due to were associated with move 3 step 2, and 22 bundles such as are consistent with, and studies suggest that were associated with move 4 step 1. Apart from these, the results also demonstrated that most lexical bundles are expressed using (Premodifier) Noun phrase + Verb phrase + complement followed by (Premodifier) Copula be + noun/adjectival phrases. Interestingly, the study found new structural categories such as *Noun phrase + passive + (to phrase fragment) and Other noun phrases. To conclude, the analysis of MRAs discussion section in the present study provides insights into how high impact factor RAs published in high impact journals are written and structured. More importantly, the study yielded two key outcomes. One is the modified framework of rhetorical moves in the discussion section which could be used by future researchers. The second is the generation of a lexical bundle list that is typical to the moves and steps of the discussion.